2010
DOI: 10.1051/0004-6361/200913535
|View full text |Cite
|
Sign up to set email alerts
|

The activity of comet C/2007 D1 (LINEAR) at 9.7 AU from the Sun

Abstract: Aims. We report on the unusual distant activity of the dynamically new comet C/2007 D1 (LINEAR), observed at r h = 9.7 AU postperihelion. This comet is particularly interesting because of its quite large perihelion distance (r q = 8.8 AU). Methods. We analyse V and R band images taken at the TNG telescope to characterise the dust coma of the comet and investigate its photometry, colours, and dust production.Results. The colour of the dust is redder than the Sun (V − R = 0.505 ± 0.093 at the photometric apertur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In 2009 we started an observational programme for a systematic investigation of the distant dust environment of several LPCs at very large heliocentric distances, beyond the "water" zone. The comet C/2007 D1 (LINEAR) (Mazzotta Epifani et al 2010) was observed among the sample, and its exceptional activity at almost 10 AU post-q was promptly reported.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…In 2009 we started an observational programme for a systematic investigation of the distant dust environment of several LPCs at very large heliocentric distances, beyond the "water" zone. The comet C/2007 D1 (LINEAR) (Mazzotta Epifani et al 2010) was observed among the sample, and its exceptional activity at almost 10 AU post-q was promptly reported.…”
Section: Introductionmentioning
confidence: 87%
“…In the recent past, the distant dust environment of the comets C/2003 O1 (LINEAR) at 7.4 AU post-q (Mazzotta Epifani et al 2009) and C/2007 D1 (LINEAR) at 9.7 AU post-q (Mazzotta Epifani et al 2010) has been quantitatively studied, deriving unexpectedly high dust production rates (∼30 kg s −1 and >500 kg s −1 , respectively), of the same order of magnitude A&A 561, A6 (2014) or even larger than that of old periodic comets at much smaller heliocentric distances (see, e.g., Mazzotta Epifani & Palumbo 2011). Unfortunately, very few similar studies for LPCs on their pre-q orbital branch are presently available.…”
Section: Introductionmentioning
confidence: 99%
“…The photometric method, derived from the method used by Jewitt (2009) to compute the dust production rate of active Centaurs in the region between 5 and 12 au, has been adapted and already successfully applied by our group to several active minor bodies such as long-period comets (Mazzotta Epifani et al 2010, 2014b), short-period comets (Mazzotta Epifani & Palumbo 2011), and active Centaurs (Mazzotta Epifani et al 2011, 2014a. The model relates the optical photometry to the dust production rate via some realistic assumptions on the comet-like dust environment, in particular on the power-law dust size distribution and the dust outflow velocity.…”
Section: Faint Activity and Nucleus Sizementioning
confidence: 99%
“…3 in Mazzotta To obtain a first-order quantitative estimate of the dust massloss rate for the centaur P/2010 C1 (Scotti), we applied a "photometric model", which relates the optical photometry to the dust production rate via some realistic assumptions on the cometlike dust environment. The method is derived from the one used by Jewitt (2009) to compute the dust production rate of active Centaurs in the region between 5 and 12 AU, and was adapted and already successfully applied by our group to several active A69, page 6 of 8 minor bodies such as long period comets (Mazzotta Epifani et al 2010, 2014, short period comets (Mazzotta , and active Centaurs .…”
Section: Afρ and Dust-mass Production Ratementioning
confidence: 99%